Expert consensus on the conservative management of patients with chronic venous disease in CEAP clinical classes C0s-C3 in Italy. (June 2020) - Vitale, Cristiana; Lucchi, Massimo; Bissacco, Daniele; Bilancini, Salvino; D'Abate, Fabrizio; Santoliquido, Angelo
Objectives: To define a consensual approach for the conservative treatment of patients C0s-C3. Method: The project was structured into two phases. The first one involved a group of Italian specialists in angiology and/or vascular surgery with the aim to compare their therapeutic choices in the management of patients in CEAP C0s-C3. The second phase used a Delphi consensus in order to elaborate practical statements on the conservative management of these patients. Results: The first phase involved a group of 166 Italian specialists while the second phase involved a Steering Committee of 6 specialists and a panel of 20 specialists. At the end of the third round, a consensus >80% was reached on seven assertions. Conclusion: Seven statements have been drafted by a group of Italian specialists to provide physicians with practical guidance for the conservative treatment of C0s-C3 patients. Outstanding issues on the management of these patients were identified, confirming the urgent need of further research.